Transforming History Teaching with Tablets: Teacher Preparedness and Student Engagement in Bagamoyo District, Tanzania - Adam Kiimbe; Prospery M. Mwila (PT. Pusmedia Group Indonesia, 2026)
The integration of educational tablets in secondary school classrooms has emerged as a key strategy for transforming history teaching and learning in Tanzania. This study explored how tablets influence instructional techniques, teacher preparedness, and student engagement among history teachers in public secondary schools in Bagamoyo District. A mixed-methods approach employing a convergent parallel design was adopted, combining quantitative questionnaires and qualitative interviews with 30 teachers, including both history specialists and general academic staff. Findings indicate that tablets enhance lesson planning by providing access to multimedia resources, digital notes, interactive materials, and structured learning paths, allowing teachers to design more adaptive and student-centered lessons. Tablets also strengthen teacher preparedness by supporting historical research, collaborative lesson development, formative assessment, and classroom management, while fostering pedagogical innovation and confidence in content delivery. In addition, tablet-based tools such as digital exhibitions, interactive timelines, and multimedia presentations facilitate teachers’ engagement with history content, improving comprehension, critical thinking, and instructional effectiveness. Challenges identified include limited device availability, inconsistent internet connectivity, insufficient training, and unclear policy guidance, which constrain optimal tablet utilization. Addressing these barriers requires investment in infrastructure, professional development, policy frameworks, and localized, curriculum-aligned digital resources. By enabling interactive, participatory, and inquiry-driven learning, tablets contribute to transforming traditional history classrooms into dynamic environments that support 21st-century educational goals. The study highlights the potential of technology to enhance teacher competence, instructional quality, and student learning outcomes when integrated thoughtfully within pedagogical practices.